2018
DOI: 10.1051/0004-6361/201834181
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-propagator approach to compute fluid Love numbers and applicability to extrasolar planets

Abstract: Context. The mass and radius of a planet directly provide its bulk density, which can be interpreted in terms of its overall composition. Any measure of the radial mass distribution provides a first step in constraining the interior structure. The fluid Love number k 2 provides such a measure, and estimates of k 2 for extrasolar planets are expected to be available in the coming years thanks to improved observational facilities and the ever-extending temporal baseline of extrasolar planet observations. Aims. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 39 publications
(58 reference statements)
2
32
0
Order By: Relevance
“…Beyond the mass‐radius relations in use today, moment of inertia ( I ) and fluid Love number ( k 2 ) will not be affected by differences of the magnitude suggested here (Padovan et al, ). The robust behavior of the iron EOS offers the opportunity to reliably invert observational data of I and k 2 , which are within reach of astronomical observations (Batygin et al, ; Biersteker & Schlichting, ; Csizmadia et al, ), for first‐order planetary structure such as R core / R planet (Padovan et al, ).…”
Section: Density In Super‐earth Coresmentioning
confidence: 69%
“…Beyond the mass‐radius relations in use today, moment of inertia ( I ) and fluid Love number ( k 2 ) will not be affected by differences of the magnitude suggested here (Padovan et al, ). The robust behavior of the iron EOS offers the opportunity to reliably invert observational data of I and k 2 , which are within reach of astronomical observations (Batygin et al, ; Biersteker & Schlichting, ; Csizmadia et al, ), for first‐order planetary structure such as R core / R planet (Padovan et al, ).…”
Section: Density In Super‐earth Coresmentioning
confidence: 69%
“…We considered a planetary Love number k 2 = 0.5 based on recent models (Wahl et al 2016), and forced k 3 = k 4 = 0. Indeed, Padovan et al (2018) showed that k 2 has the strongest dependence on central mass concentration among the three. We highlight that only synthetic light curves were created to prove the feasibility of our method, not real data, thus our results should not be physically interpreted in terms of, e.g., internal structure.…”
Section: Retrieval Of K 2 In Transit Light Curvesmentioning
confidence: 99%
“…In particular, the second-degree Love number, k 2 , is an indication of mass concentration towards the body's center, providing additional information about the interior (see, e.g., Kellermann et al 2018). A value of k 2 = 0 indicates a mass-point approximation (a.k.a., Roche model), k 2 = 1.5 corresponds to a fully homogeneous body, and its full derivation depends on the internal radial den-arXiv:1905.03171v1 [astro-ph.EP] 8 May 2019 sity profile, (see, e.g., Padovan et al 2018). As a result of tidal and rotational deformations, the stellar eclipsed area during transit will differ from a transiting sphere, modifying the corresponding transit light curve ).…”
Section: Introductionmentioning
confidence: 99%
“…They depend on the timescale of the perturbation and on the rheological properties of the interior (i.e., radial density profile, elastic properties, viscosity). For example, the rotational figure of the Earth is relaxed, i.e., it attained hydrostatic equilibrium and accordingly, its shape can be parameterized using fluid Love numbers (Padovan et al 2018). At the same time, on the shorter tidal lunar and solar timescales, the response is described by tidal Love numbers (e.g., Petit & Luzum 2010).…”
Section: Introductionmentioning
confidence: 99%